2021
DOI: 10.3201/eid2701.191791
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Acute Rheumatic Fever and Rheumatic Heart Disease among Ethnic Groups, New Zealand, 2000–2018

Abstract: These conditions disproportionately affect Māori and Pacific Islanders, particularly those living in high socioeconomic deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 22 publications
6
63
0
1
Order By: Relevance
“…Pacific Peoples under the age of 20 years were seven times more likely to have GAS detected in a skin swab and 70 times more likely to be hospitalised for ARF than European/Other ethnicities. These stark inequities mirror previously published ARF rates, which reported that between 2000-2018 Pacific Peoples (5–14 years of age) had the highest national hospitalisation rates for ARF (80 cases per 100,000 population), with these ARF incidence rates continuing to increase each year [ 11 ]. In addition, GAS detection in skin swabs and ARF rates were highest for those living in the most socio-economically disadvantaged areas.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Pacific Peoples under the age of 20 years were seven times more likely to have GAS detected in a skin swab and 70 times more likely to be hospitalised for ARF than European/Other ethnicities. These stark inequities mirror previously published ARF rates, which reported that between 2000-2018 Pacific Peoples (5–14 years of age) had the highest national hospitalisation rates for ARF (80 cases per 100,000 population), with these ARF incidence rates continuing to increase each year [ 11 ]. In addition, GAS detection in skin swabs and ARF rates were highest for those living in the most socio-economically disadvantaged areas.…”
Section: Discussionsupporting
confidence: 83%
“…Rates of ARF and RHD within NZ are significantly higher than rates in other high-income countries, such as the USA and those in Europe [6] , [7] , [8] . ARF occurs almost exclusively within indigenous Māori and Pacific Peoples in NZ, highlighting a pattern of inequities across a range of health indicators for these populations; however, the gradient is far more marked than for any other health condition [8] , [9] , [10] , [11] . The reasons for this extreme disparity for ARF between populations in NZ remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ARF rates for indigenous Australian, New Zealand Māori, and Pacific Islander populations are among the highest in the world ( 12 , 13 ). In New Zealand, deaths from ARF are uncommon, but RHD causes ≈140 deaths and 600 hospitalizations annually; Māori and Pacific Islander persons are overrepresented ( 14 ).…”
mentioning
confidence: 99%
“…Approximately 60% of ARF cases progress to chronic rheumatic heart disease (RHD), which can cause permanent heart valve damage (3), with an estimated 33 million people living with RHD globally (4). Although ARF rates declined over the twentieth century, the disease persists in low-income countries and amongst disadvantaged communities in some high-income countries, with Indigenous Maōri and Pacific children in New Zealand and Aboriginal children in Australia having some of the highest incidences in the world (5,6).…”
Section: Introductionmentioning
confidence: 99%